Assessing prison adjustment among young adult offenders: Changes, correlates, and outcomes - Gonçalves, Leonel C. (European journal of criminology, 2021)
This longitudinal study investigated the self-reported adjustment of 75 young adults (aged 17-22 years) newly admitted to a Portuguese prison, and examines changes, correlates, and outcomes of their prison adjustment. The prisoners were assessed at the first, third, and sixth month after their entry in prison. Regression analyses revealed that, overall, adjustment problems remained relatively stable during the first six months of incarceration. Having more prison visits, a lower educational level, and being White were associated with more adjustment problems in general. Adjustment problems were, in turn, associated with subsequent mental health symptoms and severe disciplinary infractions. The current study shows that self-report measures may be useful in assessing the adjustment of young adult offenders’ over time in prison.